Socio-economic Determinants of Smoking Prevalence and Intensity in Nepal - Adhikari, Naveen; GC, Shreezal; KC, Subin; Raut, Nirmal Kumar (Economic Journal of Development Issues, 2022)
This study examines the socioeconomic determinants of smoking and smoking intensity in Nepal. Leveraging data from the nationally representative Nepal Multiple Indicator Cluster Survey 2019, a logistic regression is utilized to identify predictors of individual smoking while the study relies on Poisson estimation technique to examine the determinants of smoking quantity. Our results indicate that individual characteristics—particularly age, level of education, history of alcohol use, and consumption of smokeless tobacco—play a significant role in predicting the prevalence of smoking. On the other hand, household factors like wealth scores, household size, and house-specific attributes are only weakly associated with both smoking behavior and intensity. Our results also support that similar set of socio-economic variables influence the likelihood of smoking and the quantity of cigarettes consumed. These findings emphasize the need for demand-side interventions targeted to specific socioeconomic groups, and supplementing the existing supply-side policy and regulatory measures implemented by the Government of Nepal.